2016
DOI: 10.1103/physrevb.93.075144
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit excitations and electronic structure of the putative Kitaev magnetαRuCl3

Abstract: Mott insulators with strong spin-orbit coupling have been proposed to host unconventional magnetic states, including the Kitaev quantum spin liquid. The 4d system α-RuCl3 has recently come into view as a candidate Kitaev system, with evidence for unusual spin excitations in magnetic scattering experiments. We apply a combination of optical spectroscopy and Raman scattering to study the electronic structure of this material. Our measurements reveal a series of orbital excitations involving localized total angul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
163
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(191 citation statements)
references
References 58 publications
25
163
3
Order By: Relevance
“…The recent optical absorption experiments for α-RuCl 3 have found a dominant peak around 1.2 eV as well as a small additional peak near 0.3 eV [32,57]. The photoemission spectroscopy measurement has also observed a large gap about 1.2 eV [58].…”
mentioning
confidence: 84%
“…The recent optical absorption experiments for α-RuCl 3 have found a dominant peak around 1.2 eV as well as a small additional peak near 0.3 eV [32,57]. The photoemission spectroscopy measurement has also observed a large gap about 1.2 eV [58].…”
mentioning
confidence: 84%
“…All of the configurations become insulator with the gap of ∼ 1 eV between the lower and upper Hubbard bands at U eff = 2 eV. DOS for the resulting phases are almost identical to the one from single-layer calculation 10 and show no significant difference compared to each other, so we do not present the DOS plots here. Table III shows the optimization results.…”
Section: Stacking With Zigzag Magnetic Ordermentioning
confidence: 99%
“…One promising candidate is α-RuCl 3 , where edge-sharing RuCl 6 octahedra form two-dimensional RuCl 3 layers in which Ru honeycomb layers reside [3][4][5][6][7][8][9][10][11] . Compared to its 5d transition metal oxide counterparts α-A 2 IrO 3 (A=Li,Na) [12][13][14][15][16] , α-RuCl 3 has closer-to-ideal RuCl 6 octahedra 3 , so it was proposed as an excellent platform to explore the Kitaev physics and related magnetism despite weaker SOC 4,9,11,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a remarkable theoretical and experimental progress has been achieved in understanding that fractionalization is one of the most promising hallmarks of a QSL. Indeed, it has been demonstrated that fractionalized excitations, which are Majorana fermions and Z 2 gauge fluxes for KSLs, can be probed by conventional spectroscopic techniques, such as inelastic neutron scattering (INS) [26,[31][32][33][34], Raman scattering with visible light [21,25,[35][36][37][38][39], and resonant inelastic X-ray scattering (RIXS) [40][41][42].…”
mentioning
confidence: 99%
“…The Kitaev spin liquid (KSL) on the honeycomb lattice [3] and its generalizations on tricoordinated threedimensional (3D) lattices [4][5][6][7][8] are quintessential examples of such QSL phases. Importantly, recent years have seen much progress in identifying a large number of candidate materials for realizing these KSL phases [9][10][11][12], such as the honeycomb iridates Na 2 IrO 3 [13][14][15][16][17][18] and α-Li 2 IrO 3 [19], the honeycomb ruthenium chloride α-RuCl 3 [20][21][22][23][24][25][26], and the 3D harmonichoneycomb iridates β-and γ-Li 2 IrO 3 [27][28][29][30].…”
mentioning
confidence: 99%